Azadirachta indica: Antibacterial activity of neem against different strains of bacteria and their active constituents as preventive in various diseases - Herrera-Calderon, Oscar (2019)
Neem has become valuable plant in the world which shows the solutions for hundreds to thousands problems. Azadirachta indica (Neem) is a rapidly growing evergreen well known tree found Pada generally in various regions of world like America, Africa and India. It has been widely used in Chinese, Ayurveda and Unani medicines across the world especially in Asians countries for the prevention and treatment of diseases. The different parts of neem plant contain biological compounds responsible for antibacterial, antiviral and antifungal activities. It is considered as safe medicinal plants and modulates the numerous biological processes without any adverse effect. Neem tree produces some active compounds which contain biological activities, parts of neem tree such as Root, bark, leaf, flower, seed and fruit together possesses biological activities. Various compounds have been obtained from various parts of neem. Biological activities of few of them have been studied. Hence, the article is aims to utilize the medicinal properties of whole neem plant in various disorders of mankind. © 2019 Phcogj.Com.